On-Treatment Elevation in Hepatic Transaminases during HCV Treatment with Ombitasvir, Paritaprevir, Dasabuvir, Ritonavir, and Ribavirin: A Case Series. (26th May 2016) - Bean, Madelyne; Tang, Lydia; Kottilil, Shyam; Beavers, Kimberly L.; Meissner, Eric G.
Abstract : Eradication of chronic hepatitis C virus (HCV) infection is now possible with all oral antiviral medications, including the combination of ombitasvir, paritaprevir, dasabuvir, and ritonavir (PrOD) with or without ribavirin. While high rates of sustained virologic response (SVR) can be achieved, a small subset of patients experience on-treatment liver enzyme elevations, in particular women using concurrent estradiol-containing oral contraceptive medications (OCPs). Herein, we describe four cases of liver enzyme elevations within 2-3 weeks of PrOD initiation in African-American men infected with HCV genotype 1a or 1b. Three patients with varying degrees of hepatic fibrosis received a full treatment course without medication modification, achieved SVR, and experienced resolution of liver enzyme abnormalities. One patient with cirrhosis was switched mid-treatment to an alternate HCV regimen, experienced subsequent resolution of liver enzyme abnormalities, and achieved SVR. In summary, these cases suggest that all HCV patients treated with PrOD, independent of gender or concurrent medications, should have laboratory monitoring for liver enzyme elevations, with a particular emphasis on early monitoring in cirrhotic patients.